Estado nutricional en personas discapacitados asociado a problemas con la ingesta alimentaria, que acudieron a la unidad básica de rehabilitación profesional – EsSalud – Trujillo, en el periodo julio- septiembre 2007 - Peralta Tingal, Elena Elizabeth (2008)
The nutritional status was determined in disabled people with problems associated with dietary intake, who attended the Vocational Rehabilitation Unit Basic - ESSALUD - Trujillo, in the period July-September 2007, the population was comprised of 260 patients with disabilities and shows consisted of 71 patients, representing 27.31% of the total population. To assess the nutritional status was used as a method, BMI, Cardiovascular Risk, percentage of fat and protein reserves to normal population, regardless of the type of disability submit, because of a lack of valuation methods for people with disabilities. In addition, we studied the influence of certain nutritional problems that could be affecting negatively on the nutritional status of the population, and inadequate intake or poor, trouble swallowing food and other: diarrhea, constipation, vomiting, diarrhea and gas. The 50% of the population presented malnutrition among both males and females, affecting a greater proportion of patients with motor disabilities or mental respectively and those older than 55 years. The problems with the dietary intake influence the nutritional status of the population, similar for both genders, affecting in equal shares to all types of disabilities and those older than 55 years